Conceptualization of Negative Attitudes towards People with Schizophrenia in Turkey - Umucu, Emre (European Journal of Mental Health, 2019)
Previous studies have shown that stigmatizing attitudes toward individuals with schizophrenia are common in Turkey, and Turkish society has a tendency to reject such individuals. The purpose of this paper, therefore, is to provide an overview of negative attitudes towards people with schizophrenia in Turkey. A systematic search of the literature in Academic Search Complete, CINAHL, ERIC, MEDLINE, and PsycINFO was performed to review these negative attitudes. Six major themes were identified in 32 studies: (a) health care providers’ negative attitudes, (b) family’s and caregivers’ negative attitudes, (c) the public’s negative attitudes, (d) students’ negative attitudes, (e) perceived and internalized stigma, and (f) stigma reduction. The results supported the hypothesis that health care providers, caregivers and families, the public and students have negative attitudes toward people with schizophrenia, which is consistent with the results of studies conducted worldwide.